Social media wellness : helping tweens and teens thrive in an unbalanced digital world - Homayoun, Ana (Corwin Teaching Essentials., 2018)
Todays students face a challenging paradox: the digital tools they need to complete their work are often the source of their biggest distractions. Students can quickly become overwhelmed trying to manage the daily confluence of online interactions with schoolwork, extracurricular activities, and family life. Written by noted author and educator Ana Homayoun, Social Media Wellness is the first book to successfully decode the new language of social media for parents and educators and provide pragmatic solutions to help students: Manage distractions, focus and prioritize, improve time-management, become more organized and bookst productivity, and decrease stress and build empathy. With fresh insights and a solutions-oriented perspective, this crucial guide will help parents, educators and students work together to promote healthy socialization, effective self-regulation, and overall safety and wellness -- Amazon.